Common mycorrhizal networks asymmetrically improve chickpea N and P acquisition and cause overyielding by a millet/chickpea mixture - Li, Chunjie; Li, Haigang; Hoffland, Ellis; Zhang, Fusuo; Zhang, Junling; Kuyper, Thomas W. (Plant and soil, 2022)
Aim Cereal/legume intercropping often increases yield, partly because of increased nitrogen (N) and phosphorus (P) acquisition. The aim of this paper was to investigate the role of arbuscular mycorrhizal (AM) fungal common mycorrhizal networks (CMNs) in overyielding by the millet ( Setaria italica L.) and chickpea ( Cicer arietinum L.) mixture and to find out if the effect of a CMN depends on which of the two species was first colonized by AM fungi (AMF). Methods Microcosms with two compartments were used, separated by a 30-μm nylon mesh. Both compartments contained either chickpea or millet, in monoculture or mixed. One or none of the two compartments was inoculated with the AMF species Funneliformis mosseae . The plant in the inoculated compartment was referred to as the donor, and the plant in the neighboring, non-inoculated compartment as the receiver. Results Inoculation in one compartment resulted in mycorrhiza formation in the other compartment, providing evidence for the formation of CMNs. Inoculation of chickpea in the mixture increased N and P acquisition and biomass of both chickpea (donor) and millet (receiver) leading to overyielding of the mixture, whereas inoculation of millet increased biomass of chickpea (receiver) only, but did not increase N or P acquisition by any of the two species, and there was no overyielding. Chickpea as donor had higher numbers of phosphate-solubilizing bacteria in its rhizosphere compared to chickpea as receiver. The shoot N:P ratio of chickpea as donor was lower than as receiver. Conclusion Our study demonstrated asymmetry in nutrient gains by a mixture of a cereal and a legume, dependent on which plant species was the donor or receiver. This suggests that initiating mycorrhizal networks by legumes in intercropping could be an important factor contributing to the magnitude of the intercropping effect.